Pengembangan Buku Referensi Biologi Berdasarkan Hasil Identifikasi Keanekaragaman Morfologi Famili Araceae di Wisata Alam Pinus Sigrowong Kabupaten Temanggung : (Development of Biology Reference Book Based on the Identification of Morphological Diversity of Araceae Family in Sigrowong Pine Nature Tourism Temanggung Regency) - Ardenia, Silvia; Permadani, Karunia Galih; Ramadhani , Shefa Dwijayanti (BIODIK, 2024)
Research on the Araceae family has not been done much, especially in the field of education. These plants have extraordinary adaptability due to their unique morphological structure. Sigrowong Pine Nature Tourism Area of Temanggung Regency has local potential in the diversity of the Araceae Family. The potential of this plant has also not been fully used in the learning process, so it is important to be informed and utilized in learning. Widespread dissemination of information and its utilization in learning is very important to increase awareness of the importance of maintaining and preserving the existence of Araceae family plants. The utilization of local potential as a learning resource is still not optimal, which is indicated by Biology Education students of Tidar University who have not used local potential-based learning resources and the lack of variety of reference books used in learning Plant Biosystematics courses. The selection of learning resources is based on the needs of students to develop local potential-based reference books. This study aims to determine the feasibility of biology reference books developed from the results of species identification and morphological diversity of the Araceae Family in Sigrowong Pine Nature Park, Temanggung Regency. The development model used is 4-D developed by Thiagajaran and further modified into 3-D. Data collection was carried out by observing the Araceae Family in Sigrowong Pine Nature Park and identifying morphological characteristics. Analysis of the feasibility of reference books using a book feasibility validation sheet. There are 16 species of Araceae Family with different morphological characteristics for each species. The results of the material expert validator's research on the developed reference book were 93.75% with a very feasible category and a media expert of 97.5% with a very feasible category. The results of the readability test by students were 84.2% with a high category and the results of the feasibility and usefulness test by the lecturer teaching the Plant Biosystematics course were 93.10% with a very feasible category. Based on the data obtained from the validation results, readability test, and feasibility test, the reference book developed is very feasible to use. Abstrak. Penelitian ini bertujuan untuk mengevaluasi kelayakan buku referensi biologi yang dikembangkan dari identifikasi jenis dan keanekaragaman morfologi Famili Araceae di Wisata Alam Pinus Sigrowong, Kabupaten Temanggung. Metode pengembangan yang digunakan adalah model 4D oleh Thiagarajan, yang diterapkan hingga tahap 3D: Define, Design, dan Develop. Tahap Define dilakukan melalui studi pendahuluan dengan observasi dan analisis permasalahan. Tahap Design bertujuan merancang buku referensi biologi untuk identifikasi tanaman Famili Araceae di Wisata Alam Pinus Sigrowong. Tahap Develop menghasilkan produk final yang telah disusun dan dikembangkan berdasarkan revisi dan masukan. Hasil pengembangan buku referensi biologi mengenai keanekaragaman morfologi Famili Araceae di Wisata Alam Pinus Sigrowong mengidentifikasi 16 spesies dengan variasi morfologi. Pada tahapan pengembangan buku didapatkan masalah bahwa masih kurangnya literatur yang berbasis potensi lokal dan kurangnya pemahaman oleh mahasiswa mengenai morfologi tumbuhan. Buku terdiri dari lima bagian: cover depan, bagian awal, bagian inti, bagian akhir, dan cover belakang. Hasil penilaian pada tahap pengembangan menurut validator ahli materi adalah sebesar 93,75% dengan kategori “sangat layak”, sedangkan menurut validator ahli media sebesar 97,5% dengan kategori “sangat layak”, untuk hasil uji keterbacaan oleh mahasiswa sebesar 84,2% dengan kategori “tinggi”, dan hasil uji kelayakan oleh dosen Biosistematika Tumbuhan sebesar 93,10% dengan kategori “sangat layak”. Pengembangan buku referensi ini bertujuan sebagai sumber belajar alternatif untuk mahasiswa dan masyarakat umum, memperkenalkan potensi lokal Wisata Alam Pinus Sigrowong. Buku ini juga berfungsi sebagai referensi bagi pendidik, dosen, dan peneliti dalam mengembangkan sumber belajar yang kreatif, inovatif, dan efektif, serta mendukung pemanfaatan potensi lokal.